Gambaran Tahapan Pergolakan Emosi Dalam Novel Serangkai: Perspektif Psikologi Kematian E. Kuebler-Ross - Amaliyah, Rosikha; Dwi Turistiani, Trinil (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
Death is inevitable. All living things in this world will die. Death does not discriminate by age, social status, or gender. Everything is predetermined by God; it is up to us to determine how we prepare for it. Death is a state of total loss of life. Our spirit is no longer within our body. Psychology is defined as: a science that studies behavior and mental processes. Psychology not only examines human life after death, but also often studies the attitudes and perspectives people take on the issue of death, as well as the psychological state of humans at the moment of death. Therefore, the psychology of death is a person's perspective on death, both before and after that moment. In this article, I discuss the relationship between cathartic novels and the psychology of death.